Tinjauan Literatur tentang Upaya Optimalisasi Waktu Pergantian Mold Menggunakan SMED (Single Minute Exchange of Dies) - Dionisius Tegar Cahyadi; Wijayanto, Wijayanto; Riska Anggun Sucianingrum; Agus Yoga Nafasa; Muhamad Annur; Yudi Prastyo (Journal of Engineering and Applied Technology, 2025)
This study presents a qualitative literature review on efforts to optimize mold changeover time through the implementation of the Single Minute Exchange of Dies (SMED) method in manufacturing industries, particularly injection molding processes. The review synthesizes findings from national and international studies published between 2020 and 2025 to identify common problems, implementation strategies, and performance impacts of SMED. The results indicate that prolonged mold changeover time is a major contributor to machine downtime and productivity loss, mainly caused by non-standardized procedures, poor preparation, and the dominance of internal setup activities. The implementation of SMED consistently demonstrates significant reductions in setup time by separating internal and external activities, simplifying work steps, and standardizing operating procedures. Furthermore, the literature reveals that SMED contributes to improvements in production output, equipment utilization, cost efficiency, and process stability. The findings also highlight the importance of operator involvement and managerial commitment to ensure sustainable results. Overall, this review confirms that SMED is a flexible and effective approach for enhancing manufacturing performance and supporting continuous improvement initiatives.